The pathological manifestations and risks of the protectors of air conditioners in buildings - Silva, Wildson Wellington; Monteiro, Eliana Cristina Barreto (Revista ALCONPAT, 2020)
Faced with the large number of partial or total collapses in buildings, this study has the identification of the pathological manifestations and the risks of the supports for air conditioners of reinforced concrete in the buildings, the data were collected by 3D software and consolidated in the field. Of the 61 buildings analyzed, 48% are of the window model, which in a situation of degradation and fall, can reach the ground with an impact of the order of tons. In coastal regions, we add the accelerating effects of the corrosion of the reinforcement, such as high humidity, pollution by automotive vehicles and marine region. It is concluded that these supports do not have adequate structural designs, allied to the low quality and accelerating effects of the corrosion of the armature, rendering them not recoverable.